ADP Induced Depolarization of Human Platelet Membrane Potential - Wencel-Drake, June D; Feinberg, Harold (Thrombosis and Haemostasis, 1985)
The transmembrane potential of human blood platelets suspended in plasma was investigated by studying the distribution of a radiolabeled permeant ion [14C] thiocyanate. The membrane potential of resting platelets was found to be -54.50 mV ± 9.23 S.D. with a range of -39 to -76 mV (n = 27). The possibility that platelet activation alters membrane potential or that changes in membrane potential serve as an activation trigger was investigated. Stimulation by ADP (10 ¼M) resulted in a significant (p :0.05) depolarization of the membrane potential. Preincubation with 6 mM EGTA failed to inhibit ADP-induced depolarization even though EGTA effectively prevented primary and secondary aggregation but not shape change. Preincubation with PGE1 inhibited shape change, aggregation, and the ADP- induced depolarization. No significant change in membrane potential was observed following stimulation by epinephrine (50 ¼M). These results suggest that the initial interaction of ADP and its receptor may involve an inward positive current which can be determined by thiocyanate distribution.
Keywords: Human blood platelets; Transmembrane potential; Platelet activation; Thiocyanate